Virulence factors released from Porphyromonas gingivalis induce electrophysiological dysfunction in human pluripotent stem cell-derived cardiomyocytes - Soon Chul Heo; Ye Seul Kim; Yu Na Kim; Jae Ho Kim; Hyung Joon Kim (Journal of Dental Sciences, 2022)
Background/purpose: Periodontal disease development correlates with the occurrence of systemic diseases. The present study investigated the association between periodontal disease and the development of cardiac arrhythmia. Materials and methods: Human embryonic stem cell-derived cardiomyocytes (hESC-CMs) were treated with Porphyromonas gingivalis (Pg). Cardiotoxicity and electrophysiological properties of hESC-CMs were measured using the cell counting kit-8 assay and a multi-electrode array, respectively. Reverse-transcription-quantitative polymerase chain reaction (RT-qPCR) revealed the mRNA expression of S100 calcium binding protein A1 (S100A1), calsequestrin 2 (CASQ2), troponin I3 (TNNI3), myosin light chain 2 (MYL2), integrin subunit beta 1 (ITGB1), and cadherin 2 (CDH2) in hESC-CMs. Results: Treatment with Pg broth significantly decreased the beat period, field potential duration, spike amplitude, and conduction velocity without affecting the viability of hESC-CMs. In addition, the mRNA expression of CASQ2, TNNI3, and MYL2, which are all associated with calcium handling, were downregulated by Pg broth treatment. Conclusion: These findings indicate that Pg may induce cardiac arrhythmia mediated by virulence factors.